2022
DOI: 10.1007/s11356-022-20880-0
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic in the water and agricultural crop production system: Bangladesh perspectives

Abstract: The presence of high levels of carcinogenic metalloid arsenic (As) in the groundwater system of Bangladesh has been considered as one of the major environmental disasters in this region. Many parts of Bangladesh have extensively reported the presence of high levels of arsenic in the groundwater due to both geological and anthropogenic activities. In this paper, we reviewed the available literature and scientific information regarding arsenic pollution in Bangladesh, including arsenic chemistry and occurrences.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 114 publications
0
5
0
Order By: Relevance
“…For example, Chowdhury et al [74] , [75] observed that rice cultivated in Bangladesh, where the irrigation water had a high levels of As exhibited significantly higher total As content in the grain compared to rice cultivated non-As contaminated areas. Similarly, several studies have reported that rice samples from As-affected areas of West Bengal, India, had higher total As concentrations but lower proportions of methylated As species compared to rice samples from non-affected areas [76] , [77] .
Fig.
…”
Section: Uptake and Transport Of As In Rice Plantsmentioning
confidence: 83%
“…For example, Chowdhury et al [74] , [75] observed that rice cultivated in Bangladesh, where the irrigation water had a high levels of As exhibited significantly higher total As content in the grain compared to rice cultivated non-As contaminated areas. Similarly, several studies have reported that rice samples from As-affected areas of West Bengal, India, had higher total As concentrations but lower proportions of methylated As species compared to rice samples from non-affected areas [76] , [77] .
Fig.
…”
Section: Uptake and Transport Of As In Rice Plantsmentioning
confidence: 83%
“…Next, we demonstrated that P. putida and K. pneumoniae could act as bacterial sentinels for detecting arsenic. Arsenic is a prevalent and toxic heavy metal that is a global polluter of farmland 101 , 102 . We constructed an arsenic sensor by expressing the E. coli ArsR repressor 103 under control of a strong constitutive promoter (P LacIQ ) 93 and synthetic RBS 104 to ensure high levels of ArsR.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to grain As content, the lowest and highest vegetable As is recorded in Matlab north and Faridganj, respectively. There is a significant correlation between soil As concentrations and the accumulation of As in rice grains [ 90 , 91 ]. Comparable patterns of arsenic uptake in plants cultivated in regions with high soil concentrations of As and irrigated by arsenic-rich groundwater have been discovered [ 92 , 93 ].…”
Section: Resultsmentioning
confidence: 99%